PENGARUH PEMAHAMAN KURIKULUM 2013 DAN INTEGRITAS GURU TERHADAP KINERJA GURU-GURU SD KATOLIK DI MANADO - Kosmas Sobon; Jelvi M Mangundap; Stief Walewangko (STKIP Andi Matappa Pangkep, 2019)
The purpose of this research is to evaluate and analyze the understanding of the curriculum 2013 and integration on the performance of Catholic elementary school teachers in Manado City. The total of samples used are 76 respondents in 11 Catholic Primary Schools. This research is in June to July 2019. The method of the research is quantitative approach by survey methods. The results showed that (1) There is a positive influence of the understanding of the curriculum 2013 on the performance of Catholic elementary school teachers in Manado City. The effect of understanding of the curriculum 2013 on teacher performance was relatively low that is 39.1% with a significance level of 0.000 ≤ from α = 0.05. While the results of the hypothesis test knowledge variable with the t test shows the fact that t-count = 6.889 ≥ (t-tab) = 1.992. (2) There is effect of teacher’s integration on the performance of Catholic elementary school teachers with the results of the determination of percentage is 8.2% and a significance level of 0.012 ≤ from α = 0.05; (3) There is a effect of curriculum 2013 and integration simultaneously on the performance of Catholic elementary school teachers 37.5% with a significance level of 0,000 ≤ from α = 0.05.